Hepatitis B Core Antigen Impairs the Polarization While Promoting the Production of Inflammatory Cytokines of M2 Macrophages via the TLR2 Pathway - Yi, Hongyu; Zhang, Ye; Yang, Xiaofei; Li, Mengyuan; Hu, Haifeng; Xiong, Jie; Wang, Ning; Jin, Jingyi; Zhang, Yusi; Song, Yun; Wang, Xian; Chen, Lihua; et al. (Frontiers in Immunology, 2020)
Although several evidences suggesting the vital roles that innate immunity plays in the persistence and elimination of chronic hepatitis B virus (CHB) infection, the exact mechanism is still complicated. Here, we successfully polarized monocytes derived from healthy human peripheral blood mononuclear cells (PBMCs) into M1/M2 macrophages and detected the effects of hepatitis B core antigen (HBcAg) on the polarization and function of macrophages via the Toll-like receptor (TLR) 2 signaling pathway. The results showed that HBcAg had a negligible impact on M1 polarization, while it effectively impaired M2 polarization and promoted the production of pro-inflammatory cytokines such as IL-6 and TNF-α. Additionally, HBcAg treatment increased TLR2 expression on M2 macrophages and TLR2 blockade abolished the effects of HBcAg on the impaired phenotype and pro-inflammatory cytokine productions of M2 macrophages. Signaling pathway analysis revealed that the nuclear factor κB (NF-κB) pathway, the downstream of TLR2, was upregulated upon HBcAg treatment in both M1 and M2 macrophages. Furthermore, a CD8+ T-macrophage coculture system implied that compared with PBS stimulation, HBcAg-stimulated M2 macrophages regained their ability to activate CD8+ T cells with higher secretion of IFN-γ. Finally, we found impaired expression of M2-related molecules and increased levels of pro-inflammation cytokines in M2 macrophages from CHB patients upon HBcAg stimulation. In conclusion, these results imply a favourable role of HBcAg in the establishment of a pro-inflammatory microenvironment by macrophages, which may suggest a potential therapeutic strategy of HBcAg-induced macrophage activation in CHB infection.